WE7.12 The changing management of penetrating liver trauma at a tertiary referral centre in the North West of England over a 20-year period. (9th August 2022) - Reader, Harriet; Lunevicius, Raimundas
Abstract: Background: In the context of penetrating liver trauma (PLT), the liver is the second most commonly injured intra-abdominal organ. Our institution has served as a regional Major Trauma Centre (MTC) since 2012. This study aims to review trends in PLT presenting to our institution and how management has changed over time. Methods: This was a single-centre, retrospective cohort study using data obtained from the Trauma Audit and Research Network (TARN) database across a 20-year period (2000–2020). Results: 77 patients presented with PLT; 21 prior to MTC status in 2012 and 56 after. Median age was 26.8, M:F ratio was 6.9:1 and median Injury severity score (ISS) was 14. Stabbing was the most common mechanism of injury (n=53, 68.8%), followed by shooting (n=22, 28.6%). 24 patients were managed conservatively (31.2%) and 5 patients underwent angioembolisation. Prior to becoming an MTC in 2012, 19% of patients (4/21) were managed non-operatively and this increased to 50% (28/56) when the MTC was established (P < 0.05). Understandably, there was a significant increase in injury severity in the post-MTC era (mean ISS 11.75 with SD=2.8 vs 17.9 with SD=2.1). The mortality in the conservative group was 20.7% (n=6) vs 8.3% in the operative group. Overall mortality from PLT was 11.7%. Conclusion: There was a statistically significant increase in non-operative management of PLT since the MTC was established, there has been no observed increase in mortality during this period.